A kind of formaldehyde-free flame-retardant lignin adhesive and preparation method thereof

By purifying, activating and modifying lignin and combining with crosslinking agents, hyperbranched silanes and DOPO anhydrides, the problems of low utilization rate and difficult reaction of existing wood adhesives are solved, and high-performance aldehyde-free Flame retardant lignin adhesive.

CN118085814BActive Publication Date: 2025-02-25JIANGSU QINGYUN WOOD IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410226059.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-29
Publication Date
2025-02-25
Estimated Expiration
2044-02-29

AI Technical Summary

Technical Problem

In the case of shortage of petroleum resources and the hazards of free formaldehyde, the utilization rate of lignin is low and difficult to react.

Method used

By purifying, activating and modifying lignin, modified lignin is prepared and combined with crosslinking agents, hyperbranched silanes and DOPO anhydrides, forming a complex crosslinking interpenetrating network structure to improve the performance of the adhesive.

Benefits of technology

Modified lignin adhesives have good anti-aging properties, mechanical properties and flame retardant properties, and at the same time, the formaldehyde emission is low, reaching the level of aldehyde free.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a formaldehyde-free flame-retardant lignin adhesive and a preparation method thereof. The formaldehyde-free flame-retardant lignin adhesive comprises the following raw materials in parts by weight: 30-40 parts of modified lignin, 10-20 parts of water, 5-10 parts of industrial starch, 3-5 parts of a cross-linking agent, 1-2 parts of a defoaming agent, 1-2 parts of an antioxidant and 1-2 parts of a preservative. The modified lignin is obtained by purifying, activating and modifying the lignin. The hydroxyl active groups in the modified lignin react with isocyanate groups in a cross-linking agent polyphenyl polymethylene polyisocyanate during the curing process of the adhesive, so that the adhesive has certain polyurethane characteristics and has good anti-aging performance and mechanical properties. At the same time, hyperbranched silane and DOPO anhydride are introduced in the modification process to form a cross-linking network, so that the adhesive has good flame retardancy and certain anti-aging and water resistance. The introduction of a large number of amino and carboxyl groups can also improve the bonding strength of the adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of adhesives, and in particular to a formaldehyde-free flame-retardant lignin adhesive and a preparation method thereof. Background Art

[0002] Wood adhesives are indispensable in the industrial field. Urea-formaldehyde resin adhesives and phenol-formaldehyde resin adhesives are typical wood adhesives prepared from petroleum products. Although they have advantages such as good performance and low price, the increasingly scarce petroleum resources and the hazards brought by free formaldehyde cannot be ignored. Lignin is an amorphous natural polymer substance with abundant content and complex structure in nature. It is mainly composed of three different phenylpropane units connected by carbon-carbon bonds and ether bonds. It is widely distributed in plant cell walls, intercellular layers and secondary walls. Currently, most lignin on the market is extracted and synthesized from waste liquid of the pulp and paper industry or from acid hydrolyzate of fermented grass fiber.

[0003] Lignin is the only natural biomass rich in aromatic group resources in nature. It contains a variety of functional groups, such as hydroxyl, carbonyl and benzene rings. Through chemical modification and other methods, it can be used to prepare industrial raw materials with high utilization value. It is a good raw material for synthetic wood adhesives. In addition, lignin has many advantages such as abundant resources, low cost and easy biodegradation. However, the utilization of lignin is also difficult, such as excessive molecular weight, difficulty in reacting embedded active groups, large steric hindrance, etc., which leads to extremely low utilization rate of lignin. Summary of the invention

[0004] In order to solve the above problems, the object of the present invention is to provide a formaldehyde-free flame-retardant lignin adhesive and a preparation method thereof.

[0005] The purpose of the present invention can be achieved by the following technical scheme: A formaldehyde-free flame-retardant lignin adhesive comprises the following raw materials in parts by weight: 30-40 parts of modified lignin, 10-20 parts of water, 5-10 parts of industrial starch, 3-5 parts of a cross-linking agent, 1-2 parts of a defoaming agent, 1-2 parts of an antioxidant and 1-2 parts of a preservative;

[0006] The formaldehyde-free flame-retardant lignin adhesive is prepared by the following steps: adding modified lignin, water, industrial starch, defoamer, antioxidant and preservative into a stirrer, stirring and mixing at room temperature for 25-30 minutes, then adding a cross-linking agent, stirring and mixing, and obtaining the formaldehyde-free flame-retardant lignin adhesive;

[0007] The modified lignin is prepared by the following steps:

[0008] A1: Add papermaking black liquor into water, centrifuge at high speed, take the upper liquid, add sulfuric acid solution to adjust the pH value to 3, centrifuge again and filter, wash with deionized water to pH value 5-6, and vacuum dry at 80℃ for 12h to obtain purified lignin. The molar concentration of sulfuric acid solution is 3mol / L, and the ratio of papermaking black liquor to water is 100g:500mL;

[0009] A2: Add purified lignin and sodium sulfite to a container, add sodium hydroxide solution to adjust the pH value to 12, react for 2-3 hours at a stirring rate of 150-200rpm and 60°C, add glyoxal solution after cooling, stir and mix, add sodium hydroxide solution dropwise to adjust the pH value to 12, react for 4-6 hours at a stirring rate of 150-200rpm and 60°C, add hydrochloric acid solution, wash with deionized water until neutral, filter and dry to obtain activated lignin, the molar concentration of sodium hydroxide solution is 1mol / L, the mass fraction of glyoxal solution is 40%, the molar concentration of hydrochloric acid solution is 0.1mol / L, and the amount ratio of purified lignin, sodium sulfite, glyoxal solution and hydrochloric acid solution is 200-300g:50g:60-80mL:50-150mL;

[0010] During the reaction, the purified lignin is demethylated and then hydroxyethylated by sodium sulfite and glyoxal to obtain activated lignin with high activity and high hydroxyl content.

[0011] A3: Under nitrogen protection, DOPO, toluene and tetrahydrofuran are added into a container, stirred and heated to 130°C, maleic acid is added dropwise, and the mixture is reacted at a stirring rate of 200-300rpm and 130°C for 20-24h, cooled and filtered, and vacuum dried at 120°C for 12h, and then added into a container with acetic anhydride, stirred and mixed, and reacted at a stirring rate of 200-300rpm and 140°C for 10-12h, filtered, and the toluene acetic anhydride mixture is washed three times, and vacuum dried at 80°C for 12h to obtain DOPO anhydride. The volume ratio of toluene and acetic anhydride in the toluene acetic anhydride mixture is 2:1, and the amount ratio of DOPO, toluene, tetrahydrofuran, maleic acid and acetic anhydride is 1mol:100-120g:100-120g:1mol:2-3mol;

[0012] During the reaction, DOPO reacts with the double bond in maleic acid to introduce DOPO, followed by dehydration condensation to obtain DOPO anhydride, as shown below;

[0013]

[0014] A4: 3-aminopropyltriethoxysilane and deionized water are added into a container, stirred and mixed, hydrochloric acid solution is added to adjust the pH value to 5, reacted at a stirring rate of 100-200 rpm and 50°C for 4-6 hours, cooled and rotary evaporated, and vacuum dried at 60°C for 12 hours to obtain hyperbranched silane, the molar concentration of the hydrochloric acid solution is 12 mol / L, and the amount ratio of 3-aminopropyltriethoxysilane to deionized water is 50-100 g:100 mL;

[0015] During the reaction, 3-aminopropyltriethoxysilane is hydrolyzed and hyperbranched in water to form a hyperbranched polysiloxane containing a terminal amino group structure, i.e., a hyperbranched silane;

[0016] A5: Add activated lignin and deionized water into a container, stir and mix, raise the temperature to 30°C, add DOPO anhydride and hyperbranched silane, react for 1-2 hours at a stirring rate of 200-300 rpm and 40-50°C, cool and dry to obtain modified lignin. The amount ratio of activated lignin, DOPO anhydride, hyperbranched silane and deionized water is 100g: 10-15g: 30-40g: 100-150mL;

[0017] During the reaction, DOPO anhydride undergoes a ring-opening acylation reaction with the amino group in the hyperbranched silane to generate a carboxyl group, which then reacts with the hydroxyl group in the activated lignin to obtain modified lignin.

[0018] Further, the cross-linking agent is polyphenyl polymethylene polyisocyanate;

[0019] Furthermore, the defoamer is a polyether defoamer;

[0020] Further, the antioxidant is a hindered phenol antioxidant;

[0021] Furthermore, the preservative is an organic acid preservative;

[0022] Beneficial effects of the invention: The invention provides a formaldehyde-free flame-retardant lignin adhesive and a preparation method thereof, wherein the modified lignin is obtained by purifying, activating and modifying the lignin, and the hydroxyl active groups in the modified lignin react with the isocyanate groups in the cross-linking agent polyphenyl polymethylene polyisocyanate during the curing process of the adhesive, so that the adhesive has certain polyurethane characteristics and has good anti-aging and mechanical properties. The modified lignin is obtained by the ring-opening acylation reaction of DOPO anhydride with the amino group in the hyperbranched silane to generate a carboxyl group, which is then reacted with the hydroxyl group in the activated lignin, and the DOPO anhydride, the hyperbranched silane and the activated lignin are polymerized and grafted to obtain the modified lignin containing aminosiloxane groups and DOPO groups. Due to the structure of the hyperbranched silane, the modified lignin forms a complex cross-linked interpenetrating network structure, which improves the bonding strength of the adhesive, and due to the ring opening of DOPO anhydride and the grafting of the hyperbranched silane, a large number of carboxyl groups and amino groups are introduced into the modified lignin. During the use of the adhesive, it can be effectively connected to the base material, which improves the bonding peel strength of the adhesive. At the same time, the aminosiloxane group and the DOPO group will cooperate with each other under medium and high temperature conditions to form an NPC-Si flame retardant system, and then form a dense and continuous carbon layer under high temperature conditions to prevent further expansion of combustion, effectively improving the flame retardant properties of the adhesive. The introduction of the siloxane chain segment also allows the adhesive to form a Si-O-Si continuous layer after curing, which can play a certain role in corrosion resistance and water resistance. The activated lignin is obtained from papermaking black liquor after purification, demethylation and then hydroxyethylation. The activated lignin has lower steric hindrance and more active hydroxyl groups than the lignin in the papermaking black liquor. At the same time, the structure of the lignin becomes looser due to the reaction, and the internal active functional groups are fully exposed, which is beneficial to the next step of the reaction. In addition, due to the exposure of the internal active functional groups, the curing speed of the adhesive is effectively improved, and the bonding strength of the adhesive can be increased to a certain extent. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] The modified lignin is prepared by the following steps:

[0026] A1: Add the papermaking black liquor obtained by the alkali process of the papermaking industry into water, centrifuge at high speed, take the upper liquid, add sulfuric acid solution to adjust the pH value to 3, centrifuge again and filter, wash with deionized water to a pH value of 5-6, and vacuum dry at 80°C for 12 hours to obtain purified lignin. The molar concentration of the sulfuric acid solution is 3 mol / L, and the ratio of papermaking black liquor to water is 100 g: 500 mL;

[0027] A2: Add purified lignin and sodium sulfite to a container, add sodium hydroxide solution to adjust the pH value to 12, react for 2 hours at a stirring rate of 150rpm and 60°C, add glyoxal solution after cooling, stir and mix, add sodium hydroxide solution dropwise to adjust the pH value to 12, react for 4 hours at a stirring rate of 150rpm and 60°C, add hydrochloric acid solution, wash with deionized water until neutral, filter and dry to obtain activated lignin, the molar concentration of sodium hydroxide solution is 1mol / L, the mass fraction of glyoxal solution is 40%, the molar concentration of hydrochloric acid solution is 0.1mol / L, and the amount ratio of purified lignin, sodium sulfite, glyoxal solution and hydrochloric acid solution is 200g:50g:60mL:50mL;

[0028] A3: Under nitrogen protection, DOPO, toluene and tetrahydrofuran were added into a container, stirred and heated to 130°C, maleic acid was added dropwise, reacted at a stirring rate of 200 rpm and 130°C for 20 hours, cooled and filtered, vacuum dried at 120°C for 12 hours, then added into a container with acetic anhydride, stirred and mixed, reacted at a stirring rate of 200 rpm and 140°C for 10 hours, filtered, the toluene acetic anhydride mixture was washed three times, and vacuum dried at 80°C for 12 hours to obtain DOPO anhydride. The volume ratio of toluene and acetic anhydride in the toluene acetic anhydride mixture was 2:1, and the amount ratio of DOPO, toluene, tetrahydrofuran, maleic acid and acetic anhydride was 1 mol:100 g:100 g:1 mol:2 mol;

[0029] A4: 3-aminopropyltriethoxysilane and deionized water were added into a container, stirred and mixed, hydrochloric acid solution was added to adjust the pH value to 5, reacted for 4 h at a stirring rate of 100 rpm and 50°C, cooled and rotary evaporated, and vacuum dried at 60°C for 12 h to obtain hyperbranched silane, the molar concentration of the hydrochloric acid solution was 12 mol / L, and the amount ratio of 3-aminopropyltriethoxysilane to deionized water was 50 g:100 mL;

[0030] A5: Add activated lignin and deionized water into a container, stir and mix, raise the temperature to 30°C, add DOPO anhydride and hyperbranched silane, react for 1 h at a stirring rate of 200 rpm and 40°C, cool and dry to obtain modified lignin. The amount ratio of activated lignin, DOPO anhydride, hyperbranched silane and deionized water is 100 g: 10 g: 30 g: 100 mL;

[0031] Example 2

[0032] The modified lignin is prepared by the following steps:

[0033] A1: Add the papermaking black liquor obtained by the alkali process of the papermaking industry into water, centrifuge at high speed, take the upper liquid, add sulfuric acid solution to adjust the pH value to 3, centrifuge again and filter, wash with deionized water to a pH value of 5-6, and vacuum dry at 80°C for 12 hours to obtain purified lignin. The molar concentration of the sulfuric acid solution is 3 mol / L, and the ratio of papermaking black liquor to water is 100 g: 500 mL;

[0034] A2: Add purified lignin and sodium sulfite to a container, add sodium hydroxide solution to adjust the pH value to 12, react for 3 hours at a stirring rate of 200 rpm and 60°C, add glyoxal solution after cooling, stir and mix, add sodium hydroxide solution dropwise to adjust the pH value to 12, react for 6 hours at a stirring rate of 200 rpm and 60°C, add hydrochloric acid solution, wash with deionized water until neutral, filter and dry to obtain activated lignin, the molar concentration of sodium hydroxide solution is 1 mol / L, the mass fraction of glyoxal solution is 40%, the molar concentration of hydrochloric acid solution is 0.1 mol / L, and the amount ratio of purified lignin, sodium sulfite, glyoxal solution and hydrochloric acid solution is 200g:50g:60mL:50mL;

[0035] A3: Under nitrogen protection, DOPO, toluene and tetrahydrofuran were added into a container, stirred and heated to 130°C, maleic acid was added dropwise, reacted at a stirring rate of 300 rpm and 130°C for 24 hours, cooled and filtered, vacuum dried at 120°C for 12 hours, then added into a container with acetic anhydride, stirred and mixed, reacted at a stirring rate of 300 rpm and 140°C for 12 hours, filtered, the toluene acetic anhydride mixture was washed three times, and vacuum dried at 80°C for 12 hours to obtain DOPO anhydride. The volume ratio of toluene and acetic anhydride in the toluene acetic anhydride mixture was 2:1, and the amount ratio of DOPO, toluene, tetrahydrofuran, maleic acid and acetic anhydride was 1 mol:100 g:100 g:1 mol:2 mol;

[0036] A4: 3-aminopropyltriethoxysilane and deionized water were added into a container, stirred and mixed, hydrochloric acid solution was added to adjust the pH value to 5, reacted for 6 h at a stirring rate of 200 rpm and 50°C, cooled and rotary evaporated, and vacuum dried at 60°C for 12 h to obtain hyperbranched silane, the molar concentration of the hydrochloric acid solution was 12 mol / L, and the amount ratio of 3-aminopropyltriethoxysilane to deionized water was 100 g:100 mL;

[0037] A5: Add activated lignin and deionized water into a container, stir and mix, raise the temperature to 30°C, add DOPO anhydride and hyperbranched silane, react for 2 hours at a stirring rate of 300 rpm and 50°C, cool and dry to obtain modified lignin. The amount ratio of activated lignin, DOPO anhydride, hyperbranched silane and deionized water is 100g:10g:30g:100mL;

[0038] Example 3

[0039] The modified lignin is prepared by the following steps:

[0040] A1: Add the papermaking black liquor obtained by the alkali process of the papermaking industry into water, centrifuge at high speed, take the upper liquid, add sulfuric acid solution to adjust the pH value to 3, centrifuge again and filter, wash with deionized water to a pH value of 5-6, and vacuum dry at 80°C for 12 hours to obtain purified lignin. The molar concentration of the sulfuric acid solution is 3 mol / L, and the ratio of papermaking black liquor to water is 100 g: 500 mL;

[0041] A2: Add purified lignin and sodium sulfite to a container, add sodium hydroxide solution to adjust the pH value to 12, react for 3 hours at a stirring rate of 200 rpm and 60°C, add glyoxal solution after cooling, stir and mix, add sodium hydroxide solution dropwise to adjust the pH value to 12, react for 6 hours at a stirring rate of 200 rpm and 60°C, add hydrochloric acid solution, wash with deionized water until neutral, filter and dry to obtain activated lignin, the molar concentration of sodium hydroxide solution is 1 mol / L, the mass fraction of glyoxal solution is 40%, the molar concentration of hydrochloric acid solution is 0.1 mol / L, and the amount ratio of purified lignin, sodium sulfite, glyoxal solution and hydrochloric acid solution is 300g:50g:80mL:150mL;

[0042] A3: Under nitrogen protection, DOPO, toluene and tetrahydrofuran were added into a container, stirred and heated to 130°C, maleic acid was added dropwise, reacted at a stirring rate of 300 rpm and 130°C for 24 hours, cooled and filtered, vacuum dried at 120°C for 12 hours, then added into a container with acetic anhydride, stirred and mixed, reacted at a stirring rate of 300 rpm and 140°C for 12 hours, filtered, the toluene acetic anhydride mixture was washed three times, and vacuum dried at 80°C for 12 hours to obtain DOPO anhydride. The volume ratio of toluene and acetic anhydride in the toluene acetic anhydride mixture was 2:1, and the amount ratio of DOPO, toluene, tetrahydrofuran, maleic acid and acetic anhydride was 1 mol:120 g:120 g:1 mol:3 mol;

[0043] A4: 3-aminopropyltriethoxysilane and deionized water were added into a container, stirred and mixed, hydrochloric acid solution was added to adjust the pH value to 5, reacted for 6 h at a stirring rate of 200 rpm and 50°C, cooled and rotary evaporated, and vacuum dried at 60°C for 12 h to obtain hyperbranched silane, the molar concentration of the hydrochloric acid solution was 12 mol / L, and the amount ratio of 3-aminopropyltriethoxysilane to deionized water was 100 g:100 mL;

[0044] A5: Add activated lignin and deionized water into a container, stir and mix, raise the temperature to 30°C, add DOPO anhydride and hyperbranched silane, react for 2 hours at a stirring rate of 300 rpm and 50°C, cool and dry to obtain modified lignin. The amount ratio of activated lignin, DOPO anhydride, hyperbranched silane and deionized water is 100 g: 15 g: 40 g: 150 mL;

[0045] Example 4

[0046] A formaldehyde-free flame-retardant lignin adhesive comprises the following raw materials in parts by weight: 30 parts of modified lignin of Example 1, 10 parts of water, 5 parts of commercially available industrial corn starch, 3 parts of commercially available PM200 crosslinking agent, 1 part of commercially available MS-230 defoaming agent, 1 part of commercially available 3114 antioxidant and 1 part of commercially available sodium benzoate preservative;

[0047] The formaldehyde-free flame-retardant lignin adhesive is prepared by the following steps: adding the modified lignin of Example 1, water, commercially available industrial corn starch, commercially available MS-230 defoamer, commercially available 3114 antioxidant and commercially available sodium benzoate preservative into a stirrer, stirring and mixing at room temperature for 25 minutes, then adding a commercially available PM200 cross-linking agent, stirring and mixing, and thus obtaining the formaldehyde-free flame-retardant lignin adhesive;

[0048] Example 5

[0049] A formaldehyde-free flame-retardant lignin adhesive comprises the following raw materials in parts by weight: 30 parts of modified lignin of Example 2, 10 parts of water, 5 parts of commercially available industrial corn starch, 3 parts of commercially available PM200 crosslinking agent, 1 part of commercially available MS-230 defoaming agent, 1 part of commercially available 3114 antioxidant and 1 part of commercially available sodium benzoate preservative;

[0050] The formaldehyde-free flame-retardant lignin adhesive is prepared by the following steps: adding the modified lignin of Example 2, water, commercially available industrial corn starch, commercially available MS-230 defoamer, commercially available 3114 antioxidant and commercially available sodium benzoate preservative into a stirrer, stirring and mixing at room temperature for 30 minutes, then adding a commercially available PM200 cross-linking agent, stirring and mixing, and thus obtaining the formaldehyde-free flame-retardant lignin adhesive;

[0051] Example 6

[0052] A formaldehyde-free flame-retardant lignin adhesive comprises the following raw materials in parts by weight: 40 parts of modified lignin of Example 3, 20 parts of water, 10 parts of commercially available industrial corn starch, 5 parts of commercially available PM200 crosslinking agent, 2 parts of commercially available MS-230 defoaming agent, 2 parts of commercially available 3114 antioxidant and 2 parts of commercially available sodium benzoate preservative;

[0053] The formaldehyde-free flame-retardant lignin adhesive is prepared by the following steps: adding the modified lignin of Example 3, water, commercially available industrial corn starch, commercially available MS-230 defoamer, commercially available 3114 antioxidant and commercially available sodium benzoate preservative into a stirrer, stirring and mixing at room temperature for 30 minutes, then adding a commercially available PM200 cross-linking agent, stirring and mixing, and thus obtaining the formaldehyde-free flame-retardant lignin adhesive;

[0054] Comparative Example 1

[0055] Comparative Example 1 is to replace the modified lignin in Example 6 with a mixture of commercially available alkali lignin and KH-550 silane coupling agent, wherein the mass ratio of alkali lignin to KH-550 silane coupling agent in the mixture of commercially available alkali lignin and KH-550 silane coupling agent is 10 g: 1 g. The other steps are completely the same as those in Example 6, and a formaldehyde-free flame-retardant lignin adhesive is obtained;

[0056] Comparative Example 2

[0057] Comparative Example 2 is to replace the modified lignin in Example 6 with a commercially available alkali lignin and a mixture of FR-MPP nitrogen-phosphorus flame retardants, wherein the mass ratio of alkali lignin to FR-MPP nitrogen-phosphorus flame retardant in the commercially available alkali lignin and FR-MPP nitrogen-phosphorus flame retardant mixture is 10 g:1 g, and the other steps are completely the same as those in Example 6, to obtain a formaldehyde-free flame-retardant lignin adhesive;

[0058] Take the formaldehyde-free flame-retardant lignin adhesives prepared in Example 4, Example 5, Example 6, Comparative Example 1 and Comparative Example 2, and evenly apply the prepared adhesives to the single-sided wooden board surface, and then stack the coated veneers in three layers in a criss-cross pattern and put them into a hot press for hot pressing. The hot pressing temperature is 150° C., the hot pressing pressure is 1 MPa, and the hot pressing time is 10 min. The bonding strength, immersion peeling performance, bonding strength after heat aging and formaldehyde release are measured with reference to GB / T 17657-2022. The adhesive is made into a strip with a length of 200 mm, a width of 50 mm, and a thickness of 1 mm, and the flame retardant performance is tested. The specific test results are as follows:

[0059]

[0060] From the test results shown in the table, it can be seen that by comparing Example 4, Example 5 and Example 6 with Comparative Example 1 and Comparative Example 2, it can be found that after modifying the lignin and introducing hyperbranched silane and DOPO anhydride, the bonding strength, water resistance, heat resistance and flame retardancy of the adhesive are significantly improved, and the formaldehyde emission is also far below the standard, reaching the formaldehyde-free level, indicating that the modified lignin can effectively improve the bonding strength, water resistance, heat resistance and flame retardancy of the adhesive, while keeping the formaldehyde emission of the adhesive far below the standard.

[0061] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A formaldehyde-free flame-retardant lignin adhesive, characterized in that: The invention comprises the following raw materials in parts by weight: 30-40 parts of modified lignin, 10-20 parts of water, 5-10 parts of industrial starch, 3-5 parts of cross-linking agent, 1-2 parts of defoaming agent, 1-2 parts of antioxidant and 1-2 parts of preservative; The formaldehyde-free flame-retardant lignin adhesive is prepared by the following steps: adding modified lignin, water, industrial starch, defoamer, antioxidant and preservative into a stirrer, stirring and mixing at room temperature for 25-30 minutes, then adding a cross-linking agent, stirring and mixing, and then obtaining the formaldehyde-free flame-retardant lignin adhesive; The modified lignin is prepared by the following steps: A1: Add papermaking black liquor into water, centrifuge at high speed, take the upper liquid, add sulfuric acid solution to adjust the pH value to 3, centrifuge again and filter, wash with deionized water to pH 5-6, and vacuum dry at 80℃ for 12h to obtain purified lignin; A2: Add purified lignin and sodium sulfite into a container, add sodium hydroxide solution to adjust the pH value to 12, react for 2-3 hours at a stirring rate of 150-200 rpm and 60°C, add glyoxal solution after cooling, stir and mix, add sodium hydroxide solution dropwise to adjust the pH value to 12, react for 4-6 hours at a stirring rate of 150-200 rpm and 60°C, add hydrochloric acid solution, wash with deionized water until neutral, filter and dry, and then you can get activated lignin; A3: Under nitrogen protection, DOPO, toluene and tetrahydrofuran are added into a container, stirred and heated to 130°C, maleic acid is added dropwise, and the mixture is reacted at a stirring rate of 200-300 rpm and 130°C for 20-24 hours, cooled and filtered, and vacuum dried at 120°C for 12 hours, and then the mixture and acetic anhydride are added into a container, stirred and mixed, and reacted at a stirring rate of 200-300 rpm and 140°C for 10-12 hours, filtered, and the toluene acetic anhydride mixture is washed three times, and vacuum dried at 80°C for 12 hours to obtain DOPO anhydride; A4: 3-aminopropyltriethoxysilane and deionized water were added into a container, stirred and mixed, hydrochloric acid solution was added to adjust the pH value to 5, the mixture was reacted at a stirring rate of 100-200 rpm and 50° C. for 4-6 h, the mixture was cooled and rotary evaporated, and vacuum dried at 60° C. for 12 h to obtain hyperbranched silane; A5: Add activated lignin and deionized water into a container, stir and mix, raise the temperature to 30°C, add DOPO anhydride and hyperbranched silane, react for 1-2 hours at a stirring rate of 200-300 rpm and 40-50°C, cool and dry to obtain modified lignin; The cross-linking agent is polyphenyl polymethylene polyisocyanate; The antioxidant is a hindered phenol antioxidant; The preservative is an organic acid preservative.

2. The formaldehyde-free flame-retardant lignin adhesive according to claim 1, characterized in that: In step A1, the molar concentration of the sulfuric acid solution is 3 mol / L, and the ratio of papermaking black liquor to water is 100 g:500 mL; In step A2, the molar concentration of the sodium hydroxide solution is 1 mol / L, the mass fraction of the glyoxal solution is 40%, the molar concentration of the hydrochloric acid solution is 0.1 mol / L, and the amount ratio of the purified lignin, sodium sulfite, glyoxal solution and hydrochloric acid solution is 200-300 g: 50 g: 60-80 mL: 50-150 mL; In step A3, the volume ratio of toluene to acetic anhydride in the toluene acetic anhydride mixture is 2:1, and the amount ratio of DOPO, toluene, tetrahydrofuran, maleic acid and acetic anhydride is 1 mol: 100-120 g: 100-120 g: 1 mol: 2-3 mol; In step A4, the molar concentration of the hydrochloric acid solution is 12 mol / L, and the dosage ratio of 3-aminopropyltriethoxysilane to deionized water is 50-100 g:100 mL; In step A5, the ratio of activated lignin, DOPO anhydride, hyperbranched silane and deionized water is 100 g: 10-15 g: 30-40 g: 100-150 mL.

3. The formaldehyde-free flame-retardant lignin adhesive according to claim 1, characterized in that: The defoamer is a polyether defoamer.

Citation Information

Patent Citations

  • Lignin damp-proof fiberboard adhesive and producing method thereof

    CN104293287A

  • Flame-retardant epoxy resin as well as preparation method and application thereof

    CN113461907A

  • Graphene reinforced polyurethane sole and processing technology thereof

    CN115772250A